2010
DOI: 10.1017/s1755048310000040
|View full text |Cite
|
Sign up to set email alerts
|

Orthodoxy, Islam, and the Desecularization of Russia's State Schools

Abstract: This article explores the social origins and consequences of Orthodox-Muslim tensions surrounding the attempts to find a place for religion in Russia's state schools. It demonstrates that the Orthodox-Muslim tensions are an inevitable outcome of what we define as Russia's pattern of “desecularization from above.” The attempts to restore religious education are carried out by alliances of top religious and political elites, which almost by default focus on the state-run schools. These attempts run into serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…First, there was vociferous and energetic resistance from secular intellectuals, educators, opposition politicians, and human rights activists. The second type of serious resistance came from Muslim leaders (see Lisovskaya & Karpov, 2010) and other minority religious groups who feared the new arrangements would further disadvantage them by privileging Orthodoxy. Remarkably, since the criticisms came from very different angles, both sides' arguments against bringing religion into schools emphasized the constitutionally secular nature of the Russian state and Russian education, as well as the need to protect religious freedom and human rights.…”
Section: Legitimizing the New Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…First, there was vociferous and energetic resistance from secular intellectuals, educators, opposition politicians, and human rights activists. The second type of serious resistance came from Muslim leaders (see Lisovskaya & Karpov, 2010) and other minority religious groups who feared the new arrangements would further disadvantage them by privileging Orthodoxy. Remarkably, since the criticisms came from very different angles, both sides' arguments against bringing religion into schools emphasized the constitutionally secular nature of the Russian state and Russian education, as well as the need to protect religious freedom and human rights.…”
Section: Legitimizing the New Curriculummentioning
confidence: 99%
“…Russification of the republics potentially involved their Orthodoxization, further reinforcing the minority status of non-Orthodox ethnic groups. Moreover, this mixing of cultures and ethnicities within regions prepared the ground for future tensions and conflicts, including ones that surrounded religious education in public schools after the collapse of communism (Lisovskaya & Karpov, 2010).…”
Section: The Soviet Empirementioning
confidence: 99%
“…These tensions often coincide with events, such as acts of terrorism, occurring in the Russian Federation. The efforts to find a place for religion in Russian schools through alliances between political and religious elites fuelled Orthodox-Muslim tensions during attempts to de-secularise state schools from above (Lisovskaya 2010). There are also security concerns.…”
Section: A Brief Overview Of the Current Academic Research On Islam Imentioning
confidence: 99%
“…The ideology of teaching religion in the post-Soviet Russian public schools have been already examined by a number of researchers (Mitrokhin, 2000(Mitrokhin, , 2004(Mitrokhin, , 2005Glanzer, 2005;Halstead, 1994;Willems, 2007;Lisovskaya and Karpov, 2010;Shnirelman, 2011Shnirelman, , 2012Shnirelman, , 2017Köllner, 2016;Lisovskaya, 2016;Lisovskaya, 2017). It was shown that the introduction of religion-related courses is considered a visible embodiment of church-state relations, when the attempt to implement a model of church-state separation ultimately failed and "the regime increasingly drew upon the country's traditional religion not only as a source of legitimacy, but also for political support" (Marsh 2013: 20).…”
Section: Objectivesmentioning
confidence: 99%